Effectiveness of Calina Papaya Leaf Ethanol Extract on The Red Blood Profile of Wistar Rats Exposed to Cigarette Smoke - setiawan, haris; Ariesti, Wiwin (Universitas Ahmad Dahlan, 2024)
Cigarette smoke is a source of exogenous free radicals that can affect the blood. Calina Papaya leaves contain secondary metabolites that act as antioxidants. The purpose of the study was to analyze the antioxidant activity of ethanol extract of Calina Papaya leaves using DPPH method and to analyze the difference in red blood profile of wistar rats exposed to cigarette smoke after administration of Calina Papaya Leaves Ethanol Extract (CPLEE). The research method used 24 wistar rats with oral administration of CPLEE for 23 days and exposure to cigarette smoke for 15 days. There are 4 treatments, namely rats not exposed to cigarette smoke and given distilled water (K), rats exposed to cigarette smoke (KN), rats given CPLEE 100 mg/Kg BW then exposed to cigarette smoke (P1) and rats given CPLEE 200 mg/Kg BW then exposed to cigarette smoke (P2). Parameters observed were red blood profile (erythrocyte number, hemoglobin, hematocrit, MCV, MCH, MCHC, RDW). Blood was collected through the orbital sinus and analyzed using a hematology analyzer. Data were analyzed using one way ANOVA and Duncan Multiple Range Test (P<0.05). The results showed the IC50 value of the extract was 1,194.1 ppm while ascorbic acid was 22.92 ppm. The number of erythrocytes, MCV, MCH and RDW showed significant differences between groups with the highest treatment in P1. The conclusion shows that the antioxidant activity of CPLEE is very weak compared to ascorbic acid but the red blood profile (erythrocytes, MCV, MCH, MCHC, RDW) in treatment P1 is higher than other treatments.